Unveiling the links: How poverty, unemployment, education, and income inequality drive crime in Indonesia? - Kurniasih, Erni Panca; Andini, Novia; Kartika, Metasari; Dosinta, Nina Febriana; Hamsyi, Nur Fitriana; Iqbal, Ichsan (al-Uqud : Journal of Islamic Economics, 2024)
Despite a general decline in crime rates in Indonesia, the rising trends in poverty, unemployment, and income inequality in several provinces raise concerns about their potential to incite criminal behavior and escalate crime rates. This study aims to empirically examine the effects of poverty, unemployment, education, and income inequality on crime rates in Indonesia. Utilizing secondary data from the Central Statistics Agency (BPS), the study analyzes a panel dataset comprising 32 provinces over five years through panel data regression techniques. The findings reveal that poverty and unemployment have a significant and positive impact on crime rates, highlighting their critical roles as socioeconomic determinants of criminal activity. In contrast, education levels and income inequality do not exhibit significant effects on crime rates in the Indonesian context. Theoretically, these findings underscore the relevance of economic and social strain theories, which suggest that socioeconomic hardships contribute to deviant behavior as individuals seek alternative means to meet unmet needs. Practically, the study emphasizes the need for targeted poverty alleviation programs and effective unemployment reduction strategies to mitigate crime rates. Policymakers should focus on creating sustainable economic opportunities and strengthening social safety nets in vulnerable regions. This research contributes to the broader discourse on crime prevention by providing insights into the socioeconomic drivers of crime in a developing country context, guiding future strategies to foster social stability and security.